Oral health indicators in children and adolescents with cerebral palsy from specialized centers of Lima- Peru, 2012- 2013 period - Alvarez-Páucar, María Angélica (2021)
Objective. To evaluate oral health indicators in children and adolescents with cerebral palsy in Lima-Peru. Methods. An observational, descriptive and cross-sectional study of a sample of 171 patients from two specialized national referral centers for the 2012-2013 period who met the inclusion criteria. For the Greene & Vermillion oral hygiene index (OHI), decayed, missing and filled teeth (DMFT) and the dental malocclusion (DM) analysis, 126 children (6.0-11.9 years-old) and 45 adolescents (12.0-19.0 years-old) were evaluated. Results. The OHI was 2.55 (poor hygiene) in the 91.8%, regular OHI in the 8.2% and no one showed a good IHO, observing the same behavior in both age groups. The prevalence of caries was 100% and the DMFT was 4.55 ± 1.56; the children registered a DMFT of 4.52 ± 1.537 and the adolescents 4.64 ± 1.626. The DM was present in 74.3%; the children showed a 69,8% of DM and the adolescents showed 86.7%. In children, a right class I molar relationship (MR) was observed in 42.1% and a left MR in 44.4%; the adolescents showed right Class III in 42.2% and left in 37.8%. In children, the overbite (OB) was not registered in the 33.3% of the cases and it was normal in the 29.4%; the adolescents registered a normal OB in 40%. It was more frequently observed a deviation of the dental midline to the left. Conclusions. In most children and adolescents with cerebral palsy from specialized centers, a high index of DMFT caries, poor oral hygiene and the presence of malocclusions were found.